THE INFLUENCE OF AUDIT TENURE, AUDIT LAG, AND LIQUIDITY ON THE ACCEPTANCE OF GOING CONCERN AUDIT OPINION WITH FINANCIAL DISTRESS AS A MODERATION VARIABLE - Sihombing, Tanggor; Stevania, Stella (Ultimaccounting Jurnal Ilmu Akuntansi, 2024)
Abstract— This research investigates the impact of audit tenure, audit lag, and liquidity on the acceptance of going concern audit opinions with the focus on the moderating role of financial distress. This research employs logistic regression analysis to analysis secondary data from 50 manufacturing companies in Indonesia and Singapore which are included in the Health Care, Information Technology and Real Estate categories during the 2018-2022 period. The results found that audit tenure had no effect on the acceptance of going concern audit opinions, audit lag had a positive effect on the acceptance of going concern audit opinions, and liquidity had a negative effect on the acceptance of going concern audit opinions. In this research, it was also found that financial distress can weaken the negative influence of audit maturity and audit lag on the acceptance of going concern audit opinions but strengthen the positive influence of liquidity on the acceptance of going concern audit opinions. Keywords: Audit Tenure; Audit Lag; Liquidity; Going Concern Audit Opinion; Financial Distress.